Handbook of services marketing & management - Swartz, Teresa A.; Iacobucci, Dawn.; Sage eBooks (Thousand oaks, [Calif.] ; London : SAGE, 2000)
This is a comprehensive, practical and theoretical guide to the latest thinking in the foundations of services. The authors present contributions from the world's leading experts on services marketing and management.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Service industries -- Marketing; Service industries -- Management; Customer services -- Marketing; Customer services -- Management; Electronic books